Effect of the Application of Bovine and Goat Manure as a Fertilization Alternative on the Production, Nutritional Quality, and Health of African Star Grass (Cynodon nlemfuensis) at the Santa Lucía Experimental Farm, Heredia - Meza Chaves, Karla María (2024)
Livestock activity in Costa Rica triggers a growing demand for quality forage for dairy production. Fertilization, a key factor in this process, poses environmental and economic challenges for the sector. The objective of the study was to evaluate the use of bovine and caprine excreta on biomass, nutritional quality, and disease incidence in African star grass, as a nitrogen fertilization alternative in specialized dairy systems. Conducted at the Santa Lucia Experimental Farm of the National University, the study utilized a block design with three repetitions and four treatments. Biomass production was assessed by weighing harvested material, while quality and health were evaluated in the laboratory. The results show that biomass production was not reduced with excreta application, and the grass maintained its nutritional quality, making it a viable fertilization alternative. Puccinia sp. was identified as the main pathogen present in the pasture; however, its incidence is not attributed to the excreta applied. Additionally, no direct effect of the treatments was observed on the nematode population density present in the pasture.